The poem «Adam’s Dream» in the context of N. Gumilev’s works - Никитская, Екатерина Игоревна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 1970)
The article is devoted to the study of the oneiric chronotope, as a genre-forming element in the poem, and of the main sources that influenced its formation. In particular, there were revealed some links with Gumilev's occult studies and references to the visionary practices in his early works. There was also analyzed the influence of The Revelation and related genre of visions on poem’s genre specifics. In addition, there were found some parallels with the image of the oneiric sphere in older texts like "Epic of Gilgamesh" and Indian myths.